Transoral videolaryngoscopic surgery for laryngeal and hypopharyngeal cancer — Technical updates and long-term results. Issue 2 (April 2020) - Tomifuji, Masayuki; Araki, Koji; Uno, Kosuke; Kamide, Daisuke; Tanaka, Shingo; Suzuki, Hiroshi; Tanaka, Yuya; Kimura, Eiko; Hirokawa, Shotaro; Taniai, Shinichi; Shiotani, Akihiro
Abstract: Objective: Transoral videolaryngoscopic surgery (TOVS) was developed as a non-robotic procedure for en bloc laryngo-hypopharyngeal cancer resection. Straight devices had been used for this procedure, however, some cases had difficulty to reach the lesions especially in hypopharyngeal area. To overcome this problem, technical updates to facilitate transoral manipulation were developed and long term oncological and functional results were analyzed. Methods: Surgical indications were Tis, T1, T2 and selected T3 cases. In advanced T3 or T4 lesions, neoadjuvant chemotherapy was performed before surgery. Radiation failure cases (rT1 and rT2) were also indicated for TOVS. Resectable nodal involvement can be managed by combination of neck dissection. Ninety hypopharyngeal and 25 supraglottic cancer cases were retrospectively reviewed for survival analyses. In fresh hypopharyngeal cancer, 51 Stage 0–II disease and 32 Stage III-IV disease were included. In supraglottic cancer, 11 Stage I–II disease and 9 Stage III-IV disease were included. Twelve radiation failure cases were analyzed separately. As new devices, malleable forceps and malleable suction coagulator were introduced to reach the whole laryngo-hypopharynx. New curved blades for the FKWO retractor were developed and these were applied for difficult hypopharyngeal exposure cases by conventional blades. Swallowing functional outcome and risk factors for postoperative dysphagia were evaluated by univariate analysis. Results: The 5-year overall survival, disease-specific survival and larynx preservation rate of fresh hypopharyngeal cancer cases were 83.2%, 94.3% and 94.6%, respectively. Those of supraglottic cancer cases were 80%, 95% and 94.7%, respectively. Those of salvage cases were 87.5%, 87.5% and 82.5%, respectively. Those of T3 and T4 hypopharyngeal cancer treated by neoadjuvant chemotherapy with TOVS were 75.0%, 82.5% and 100% respectively. Surgical complication included bleeding (2.6%) and emergency tracheostomy (3.4%). Oral intake was maintained in 94.8% cases. By univariate analysis, patient's age (especially 80 years of age or older), larger resected area, arytenoid resection and tracheostomy were regarded as risk factors for postoperative dysphagia. Among 31 recent cases, 5 cases had difficulty in exposing hypopharyngeal lesions by conventional blades. These exposure problems were solved by curved blades. Conclusion: Using malleable devices and new curved blades for the FKWO retractor, exposure problems in the hypopharynx could be solved and TOVS could be applied in more cases. Although oncological outcomes and functional outcomes were good, patients with risk factors for dysphagia should be carefully indicated.